Development of framework for seismic response analysis of storage tank based on fault-structure system - Pokharel, Tilak; Ichimura, Tsuyoshi; Hori, Muneo; Nagashima, Toshio (Journal of Science and Engineering, 2014)
In this study, the framework for the seismic response analysis of oil-storage tank along fault-structure system concept has been presented; where the long period ground motion simulation and sloshing simulation based on 3D finite element method (FEM) is integrated. Three dimensional finite element model is constructed using multi-resolution structured and unstructured mesh for the ground motion prediction. For the sloshing analysis Lagrangian Finite Element Method is used. Also the effect of surface topography on the sloshing response is checked and the effect is found to be significant.